Redwood Bend - Carr, Robyn (Carr, Robyn. Virgin River series., 2016)
"Katie Malone and her twin boys' trip along the beautiful mountain roads to Virgin River is stopped short by a tire as flat as her failed romance. To make matters worse, the rain has set in, the boys are hungry and Katie is having trouble putting on a spare. As she stands at the side of the road pondering her next move, she hears a distinct rumble. The sight of the sexy, leather-clad bikers who pull up beside her puts her imagination into overdrive. Dylan Childress and his buddies are on the motorcycle trip of a lifetime. But the sight of a woman in distress stops them in their tracks. And while the guys are checking out her car, she and Dylan are checking out one another. In one brief moment, the world tilts on its axis and any previous plans Katie and Dylan might have had for their futures are left at the side of the road"--Publisher.